Organocatalytic Cyclization of COS and Propargylic Derivatives to Value‐Added Heterocyclic Compounds. Issue 23 (24th May 2019) - Zhou, Hui; Zhang, Rui; Mu, Sen; Zhang, Hui; Lu, Xiao‐Bing
Abstract: The organocatalytic cyclization of propargylic amines/amides with carbonyl sulfide (COS) was firstly achieved by employing COS adducts of Lewis base (LB) as organocatalysts, affording various functionalized 1, 3‐thiazolidine‐2‐ones, and 1, 3‐thiazolidine‐2, 4‐diones derivatives in a highly chemo‐ and stereoselective manner. The isotope labeling and stoichiometric experiments suggested the LB‐COS adducts preferentially mediated basic ionic pair mechanism. Furthermore, the practical application of this methodology was highlighted by the highly efficient synthesis of rosiglitazone using COS as sulfur source. Abstract : Who is this Lewis anyway ? Lewis base‐COS adducts are used for the first time as organocatalysts for the cyclization of COS with propargylic amines/amides to form functionalized 1, 3‐thiazolidine‐2‐ones, and 1, 3‐thiazolidine‐2, 4‐diones derivatives under mild conditions. The generality and functional group tolerance of this protocol is demonstrated.